PETROGRAPHIC COMPARISON OF REFRACTORY INCLUSIONS FROM DIFFERENT CHEMICAL GROUPS OF CHONDRITES - Lin Y.; Miao B.; Kimura M.; Monoi A.; Dai D. (My University, 2006)
Twenty-four refractory inclusions (40-230 μm, with average of 86 ± 40 μm) were found by X-ray mapping of 18 ordinary chondrites. All inclusions are heavily altered, consisting of fine-grained feldspathoids, spinel, and Ca-pyroxene with minor ilmenite. The presence of feldspathoids and lack of melilite are due to alteration that took place under oxidizing conditions as indicated by FeO-ZnO-rich spinel and ilmenite. The pre-altered mineral assemblages are dominated by two types: one rich in melilite, referred to as type A-like, and the other rich in spinel, referred to as spinel-pyroxene inclusions. This study and previous data show similar type and size distributions of refractory inclusions in ordinary and enstatite chondrites. A survey of refractory inclusions was also conducted on Allende and Murchison in order to make unbiased comparison with their counterparts in other chondrites. The predominant inclusions are type A and spinel-pyroxene, with average sizes of 170 ± 130 μm (except for two mm-sized inclusions) in Allende and 150 ± 100 μm in Murchison. The relatively larger sizes are partially due to common conglomerating of smaller nodules in both chondrites. The survey reveals closely similar type and size distributions of refractory inclusions in various chondrites, consistent with our previous data of other carbonaceous chondrites. The petrographic observations suggest that refractory inclusions in various groups of chondrites had primarily formed under similar processes and conditions, and were transported to different chondrite-accreting regions. Heterogeneous abundance and distinct alteration assemblages of refractory inclusions from various chondrites could be contributed to transporting processes and secondary reactions under different conditions. © The Meteoritical Society, 2006.